2013
DOI: 10.1039/c3nr33927k
|View full text |Cite
|
Sign up to set email alerts
|

Carbon nanofibers with radially grown graphene sheets derived from electrospinning for aqueous supercapacitors with high working voltage and energy density

Abstract: Improvement of energy density is an urgent task for developing advanced supercapacitors. In this paper, aqueous supercapacitors with high voltage of 1.8 V and energy density of 29.1 W h kg(-1) were fabricated based on carbon nanofibers (CNFs) and Na2SO4 electrolyte. The CNFs with radially grown graphene sheets (GSs) and small average diameter down to 11 nm were prepared by electrospinning and carbonization in NH3. The radially grown GSs contain between 1 and a few atomic layers with their edges exposed on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
83
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 118 publications
(85 citation statements)
references
References 52 publications
2
83
0
Order By: Relevance
“…1b, 34 Graphitic N atoms have the same configuration as graphitic carbon atoms, but they could introduce extra electrons in the delocalized π-system, showing a nucleophilic attack on oxygen. 1a, 35 ANCNF-800 has the largest limiting current density of −5.49 mA cm −2 among these activated samples, higher than those reported values of electrospun carbon fibers 22,36 and CNFs treated in NH 3 (Table S1), 20a and comparable to those of N-doped graphene materials prepared by annealing polypyrrole/GO, polyaniline/GO, NH 3 /GO, etc.…”
Section: Bmentioning
confidence: 60%
“…1b, 34 Graphitic N atoms have the same configuration as graphitic carbon atoms, but they could introduce extra electrons in the delocalized π-system, showing a nucleophilic attack on oxygen. 1a, 35 ANCNF-800 has the largest limiting current density of −5.49 mA cm −2 among these activated samples, higher than those reported values of electrospun carbon fibers 22,36 and CNFs treated in NH 3 (Table S1), 20a and comparable to those of N-doped graphene materials prepared by annealing polypyrrole/GO, polyaniline/GO, NH 3 /GO, etc.…”
Section: Bmentioning
confidence: 60%
“…The C900NH 3 also exhibits considerable adsorption capacity despite no activation process. This should be caused by the rough surface generated by the etching reaction of NH 3 during carbonization [27,28]. After activation, both the AC750NH 3 and AC900NH 3 show much higher N 2 adsorption capacity than the C900NH 3 .…”
Section: Resultsmentioning
confidence: 96%
“…This is caused by the high reactivity of NH 3 , which can produce active species such as atomic H, NH, and NH 2 by dissociation at high temperature. These active species can bond with the carbon atoms, increasing their mobility and thus promoting the crystallizing process [27,28]. The Raman spectra of the different samples are shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The (002) peak of the carbonized films of pure PI films became narrower and sharper. It indicated that their structures were near to that of graphite at 2θ=26.1 o [29]. 15 Meanwhile, the d-spacings calculated from (002) peaks of RGO/C composite films were 3.639, 3.735, and 3.867Å, for GO contents of 0.5wt%, 1wt% and 2wt%, respectively.…”
mentioning
confidence: 90%